Approximate and analytical bound state solutions of the Frost–Musulin potential - Adepoju, A.G.; Eweh, E.J. (Canadian journal of physics, 2014)
Despite all the attempts made by several authors to investigate the bound state solutions of the Schrödinger equation with various potentials, until now, such investigations have not been conducted for Frost–Musulin diatomic potential. In this study, we obtain the approximate bound state solution of this potential via the functional analysis method. We also numerically solved the Schrödinger equation without any approximation to centrifugal term for the same potential. The comparisons between the results reveal the accuracy of our approximate results for short-range potential.